Modeling and scheduling of utility-scale energy storage toward high-share renewable coordination - Ding, Ran; Wang, Xuanyuan; Qiu, Wei; Yao, Yiming; Xu, Haixiang; Geng, Yan; Zhuo, Zhihuan; Han, Jiayi (Frontiers in Energy Research, 2024)
As the integration of high-proportion renewable energy into the grid increases, the intermittency and uncertainty of renewable energy output significantly affect the safe and stable operation of the power system. Combining utility-scale energy storage technology with renewable coordination is one of the methods to address these issues. Compressed air energy storage (CAES) has garnered extensive attention due to its large capacity, long operational life, and clean, low-carbon advantages. Given the poor compressibility of air and its high critical point, using carbon dioxide as the working fluid in utility-scale energy storage systems can achieve higher energy storage density and cycle efficiency. Accordingly, this paper focuses on the study of utility-scale energy storage system modeling and scheduling methods considering carbon dioxide energy storage. It investigates Compressed Carbon Dioxide Energy Storage (CCES) systems, analyzes the operational framework of typical CCES systems, and sequentially establishes models for the energy storage process, energy release process, hot water tank operation, and gas storage tank operation. Based on this, it explores power system optimization dispatch methods considering CCES, incorporating the established models into an optimization dispatch model for power systems with high wind power penetration. Within the framework of a safe constraint unit commitment study, using the IEEE-30 nodes model, the effectiveness of the established models is validated. The case study results confirm the role of CCES in enhancing the absorption rate of renewable coordination. Moreover, under the same storage conditions, compared to, CCES offers greater charging and discharging power and higher energy storage density.